AVALIAÇÃO DA ATIVIDADE MOLUSCICIDA DO ÓLEO ESSENCIAL DE Citrus sinensis (L.) Osbeck FRENTE AOS CARAMUJOS TRANSMISSORES DA ESQUISTOSSOMOSE. - LEITE JÚNIOR, João de Deus da Costa (2018)
Schistosomiasis mansoni is an endemic infectious-parasitic disease caused by Schistosoma mansoni. According to the World Health Organization (WHO) one way to tackle this disease is through the population control of the Biomphalaria kind of snails, the disease intermediary vectors. Considering the importance of the discovery of new substances which present potencial molluscicide, this research has done a study on the essential oil from the peels of the Citrus sinensis (L.) Osbeck. The essential oil was extracted through the hydrodistilation technique, physical-chemical properties and the amount of the major and minor components were determined through the gaschromatography technique coupled to mass spectrometry (CG -EM). The snails used in the tests were collected at Sá Viana neighborhood in February and August, 2017, after the identification according to the adopted methodology, the snails were submitted to positivity infection tests through Schistosoma mansoni. The oil was tested with respect to toxicity testing for lethality with Artemia salina), using Dolabela criterion, and as molluscicide agent through technique proposed by World Health Organization (WHO). The results show an output (m/m) of 0,7% compared to the values of the physical-chemical properties of the essential oil studied in the literature, it was observed that there are similarities among them, in regard to the parameters examined. The chromatography analyses showed that the oil has 81,50% of d-limonene (major component) in a retention time (TR) of 7,6 minutes. The studied oil, with respect to toxicity, was considered non-toxic presenting CL 50 of 511,6 µg /mL. The essential oil molluscicide activity had a result regarding a lethal concentration of CL 50 and CL90 of 83,33 µg/mL and 168,75 µg/mL, respectively. According to the WHO criteria (1983) the studied oil is not considered ideal because it presents a bigger CL 90 value than what is established (100 µg/mL). Studies like this reveal the importance of bioactive compounds with molluscicide activity on the sustainable combat to schistosomiasis as it is a neglected desease, once been able to promote the biotechnological development through the cientific knowledge and the economical potencial of the Maranhão flora species.